Evaluating the Efficacy of a Structured Teaching Program on Intravenous Access Care Knowledge Among Nursing Students: A Pre-Experimental Study - Ejas, Umamaheswara; Rahman, Mahbubur (Journal of Educational Research and Policies, 2025)
Introduction: Intravenous access devices are used to administer fluids and medications among patients undergoing long term treatment, especially chemotherapy. Though it has many advantages, they are not free from complications such as sepsis, thrombotic complications, local tissue damage etc. Aim: The aim of the study is to evaluate the effectiveness of structured teaching programme on knowledge regarding intravenous access care among nursing students of University College of Nursing, Faridkot, Punjab. Materials and Methods: A quantitative approach with Pre- experimental (one group pre-test post-test research design) was used. The 50 samples were selected using convenient sampling technique from the University College of Nursing, Faridkot, Punjab. Self-structured knowledge questionnaire was used to assess the pre-test knowledge level and after providing structured teaching programme the post-test knowledge level was checked with the help of self-structured knowledge questionnaire after 7 days. Results: The mean score of knowledge regarding Intravenous access care was increased from 9.5 to 18.8 in the post test after structured teaching programme. The results show that there is statistically significant increase in post-test mean score after structured teaching programme. Conclusion: Hence, it is concluded that the structured teaching programme was effective. The knowledge regarding Intravenous access care among nursing students was improved with structured teaching programme.